2015
DOI: 10.1016/j.meatsci.2014.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding distiller's grains and supplementing with dietary antioxidants on ground beef color during retail display

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This was related to the myoglobin content of different fiber types. Furthermore, it has been demonstrated that antioxidant status is positively correlated with a* or color stability in the LDM of beef [27]. Cysteamine, as an excellent scavenger of oxidants hydroxyl radical and hypochlorous acid, can protect against body oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…This was related to the myoglobin content of different fiber types. Furthermore, it has been demonstrated that antioxidant status is positively correlated with a* or color stability in the LDM of beef [27]. Cysteamine, as an excellent scavenger of oxidants hydroxyl radical and hypochlorous acid, can protect against body oxidation.…”
Section: Discussionmentioning
confidence: 99%